Penatalaksanaan Fisioterapi Pada Kasus Cerebral Palsy dengan Komorbiditas Epilepsi Aktif - Desvita Savitri Kusuma Wardhani; W Wahyuni; Ika Hayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Cerebral palsy (CP) is a complex neurological disorder that often coexists with other conditions, such as active epilepsy. The interaction between these conditions can significantly impact developmental and functional outcomes in affected children. The primary objective of this study was to explore the impact of active epilepsy on the physiotherapy management of children with cerebral palsy. This study used a clinically reviewed case study approach to assess the relationship between active epilepsy and rehabilitation outcomes in children with CP. The results indicate that active epilepsy significantly impacts the developmental and functional outcomes of children with cerebral palsy. In particular, the presence of seizures can lead to increased vulnerability of neural networks, especially in critical areas such as the cerebral cortex and temporal lobe, which are important for regulating brain activity. The presence of uncontrolled seizures will negatively impact the effectiveness of rehabilitation therapy. The presence of active epilepsy in children with cerebral palsy requires rapid pharmacological intervention to reduce its effects on development and function. Effective physiotherapy management must take into account the complexity of both conditions to improve rehabilitation outcomes. Integration of targeted interventions, such as sensorimotor stimulation and movement re-patterning, is essential to improve motor control and movement quality in children.